KEPUTUSAN PEMBELIAN ONLINE TERHADAP EFEKTIVITAS IKLAN PADA KONSUMEN TRAVELOKA.COM - Ema Prasetyorini; Sandi Eka Suprajang (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2023)
The phenomenon of holding tourist activities with various touristdestinations is increasingly rife at this time, along with the growth oftechnological advances that are increasingly sophisticated, wheresomeone can directly know the location on earth. This study discussesonline purchases on the effectiveness of advertising to traveloka.comconsumers. Based on the results of the research that has been described,it can be concluded that the results of the study show that purchasingdecisions have a positive effect on the effectiveness of advertising. Thesefindings show that the higher the purchase decision, the higher theeffectiveness of advertising. The nonprobability sampling method usedin this study is purposive sampling